Antimicrobial susceptibility profiles and coagulase gene polymorphism of staphylococcus aureus isolated from bovine subclinical mastitis - Beytullah KENAR; Arzu Funda BAGCIGIL; Yahya KUYUCUOGLU; Beren Başaran KAHRAMAN; Selahattin KONAK (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2017)
The purpose of the study was to isolate Staphylococcus aureus from bovine subclinical mastitis, determine their antibiotic susceptibilities and investigate the coagulase gene polymorphism by using a PCR-based restriction fragment length polymorphism (RFLP) method. Milk samples from 463 CMT positive udders from 237 cows cultured. The antimicrobial susceptibility of the isolates were determined by disc diffusion method. A total of 82 out of the 83 isolates (98.8%) were found to be resistant at least one out of the 16 antibiotics studied. In this experiment 53 isolates (63.8%) were found to be resistant to penicillin; 52 (62.67%) to trimethoprim/sulphamethoxazole; 51 (61.5%) to ampicillin; 40 (48.2%) to erytromycin; 29 (34.9%) to tetracycline; 18 (21.6%) to ciprofloxacin, 16 (19.3%) to clindamycin, 13 (15.6%) to chloramphenicol; 8 (9.6%) to gentamicin; 5 (6.0%) to cefoxitin; 4 (4.9%) to vancomycin; 3 (3.6%) to cephalotin; 2 (2.4%) nafcillin; one (1.2%) to oxacillin and one to (1.2%) furazolidon. No imipenem resistance was seen in the S. aureus isolates. The coagulase gen polymorphism were examined by PCR amplification of coagulase gene followed by AluI digestion of repeating 81 bp DNA sequences. After nested PCR, double bands were produced in 8 of the isolates while there were single band in remaining 75 isolates. Following AluI digestion, isolates that formed single band in length of approximately 300 bp showed 3 different groups